Case Report: Non-negligible Epstein-Barr virus-associated posttransplant lymphoproliferative disorders in a lung transplant recipient - Hu, Juan; Yu, Yong-Wei; Han, Dong-Sheng; Li, Xue-Jie; Zhang, Yi-Qi; Cai, Hong-Liu; Xiao, Yong-Hong; Zheng, Xia (Frontiers in Immunology, 2023)
Background: Posttransplant lymphoproliferative disorders (PTLDs) are uncommon but serious complications in patients following solid organ transplantation. Primary Epstein-Barr virus (EBV) infection is a risk factor for the development of PTLD, especially early onset PTLD, in EBV-negative recipients. To date, however, there are no specific guidelines on the threshold of EBV-DNA load for therapeutic intervention, the source for measurement (e.g., blood, bronchoalveolar fluid), or the use of antiviral agents as prophylaxis for early PTLD prevention in EBV-mismatched patients.The present study describes a 56-year-old male lung transplant recipient diagnosed with EBV-associated PTLD.: This patient had history of invasive fungal disease and mucor and aspergillus fumigatus infections during the early stage after transplantation, necessitating antifungal therapy throughout the course of disease. The patient was EBV positive 15 days after transplantation, with lung CT showing multiple bilateral nodules of various sizes, beginning 98 days after transplantation. A lung biopsy showed PTLD and nextgeneration sequencing (NGS) revealed EBV. This patient, however, did not receive any antiviral therapy for early PTLD prevention or any PTLD-related treatment. He died 204 days after lung transplantation.The present study describes a lung transplant recipient who developed EBV-associated PTLD, a nonnegligible disease, after solid organ transplantation.Monitoring of EBV-DNA load is important, as a sudden increase may be a sensitive indicator of PTLD. Earlier diagnosis may enhance the opportunity for successful treatment.